2019
DOI: 10.1109/access.2019.2912011
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Separation Technique of Flexural Loading-Induced Acoustic Emission Sources in Railway Prestressed Concrete Sleepers

Abstract: This study determines the effectiveness and suitability of acoustic emission in order to monitor the structural health condition of railway pre-stressed concrete sleepers since the acoustic emission sensing provides effective means for detecting cracking events and quantifying the crack density. The aim of this study is two-fold. First, we establish a novel acoustic emission source separation that offers the possibility for analyzing the content of each source separately. This study is thus the first to demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…As can be seen from Figure 12, changing the modulus of elasticity has limited influence on the dynamic factors, ranging from 2.8 to 3.0. A similar finding could be reached for contact forces [51,52]. (Figure 12b) By contrast, the maximum bending moment distributions along a turnout are affected by different moduli of elasticity.…”
Section: Effects Of Sleeper Stiffnesssupporting
confidence: 78%
“…As can be seen from Figure 12, changing the modulus of elasticity has limited influence on the dynamic factors, ranging from 2.8 to 3.0. A similar finding could be reached for contact forces [51,52]. (Figure 12b) By contrast, the maximum bending moment distributions along a turnout are affected by different moduli of elasticity.…”
Section: Effects Of Sleeper Stiffnesssupporting
confidence: 78%
“…Jones and Packham [26] studied the distribution characteristics between the rolling noise and the train speed by using a microphone mounted near a smooth wheel, where the noise ranges at different speeds can support the identification of rail-head roughness. Janeliukstis and Kaewunruen [27] found that the acoustic sources of railway noise can be separated from each other, and adopted a decision tree classification algorithm to monitor the structural health of railway pre-stressed concrete sleepers.…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, the allowance of the damage factor D has been lowered to 0.5, as suggested by Hobbacher [29]. This factor is common in construction sector [46][47][48].…”
Section: Fatigue Life Assessmentmentioning
confidence: 99%